Does Valve-Sparing Repair Improve Outcomes in Tetralogy of Fallot? A Systematic Review - Jabez David John; Tirath Patel; Monica Kharat; Jeet HansalKumar Patel; Jubran Al Hooti; Zoya Riyaz Syeda; Rohit Anil Khare; Sonya Bhatia; Amin Ibrahim; Arjun Bellamkonda; Nikhilesh Anand; Bharathi S. Gadad (Journal of Cardiothoracic Surgery)
Abstract Background The systematic review determines whether valve-sparing surgeries improve patient outcomes compared with non valve-sparing surgeries for tetralogy of Fallot. Although previous studies have reported superior outcomes in valve-sparing surgery, no systematic review has compared these outcomes with those of nonsurgical surgical methods. Methods In the present research, we address this gap in the literature by comparing valve-sparing and non valve-sparing surgery outcomes. PubMed, PubMed Central, and Medline served as the databases for data collection; following the PRISMA guidelines, a comprehensive search strategy identified relevant articles for the review; the search strategy included Medical Subject heading (MeSH) terms and important keywords. The search strategy initially revealed seventy articles; these were further screened by title and abstract and refined to fifteen articles for full-text analysis. For further full-paper analysis, eight articles were refined and formed the basis of our analysis. There was a severe limitation of high-quality clinical trials and prospective studies, and we included any good-quality papers that passed the quality check and adhered to the inclusion and exclusion criteria. Results The number of patients included in this study was 962 from 8 studies; 351 underwent valve-sparing surgery, and 611 underwent TOF correction via non valve-sparing methods. This systematic review provides encouraging evidence that suggests better outcomes for valve-sparing surgery. Most studies have consistently reported a significantly lower prevalence of moderate or severe pulmonary regurgitation in valve-sparing surgeries. Since the valve-sparing technique allows for the preservation of the native valves, it allows for better growth of the pulmonary valve. Additionally, most studies reported that valve-sparing surgeries significantly improved proper ventricular function, but mixed results regarding reintervention have been reported. The risk of complications was similar between the surgical modalities; valve-sparing repair has consistently outperformed other surgical modalities. Low birth weight remains a prominent risk factor even for valve-sparing surgery. Conclusion In summary, the evidence presented in this review strongly supports the use of valve-sparing surgery for improved patient outcomes. This systematic review highlights the benefits of valve-sparing surgery over other surgical techniques. It can be a foundation for clinical practice that allows surgeons to make better, informed decisions about patient care. The limitations of the lack of studies found when this review was conducted can further guide other research, strengthen the evidence, and lead to better patient care.